STUDY OF TYPES OF INHERITANCE OF SEVERAL TRAITS OF SOFT WINTER WHEAT AND ITS COMBINING ABILITY - P. I. Kostylev; O. A. Nekrasova (Зерновое хозяйство России)
Genetic potential of productivity is a primary and essential factor in the period of formation of high productivity of winter wheat. Such quantitative traits as 1000-grain weight, a number of seeds per ear, length and width of a flag leaf are of primary importance while forming productivity of the crop. It’s possible to create a highly productive wheat variety knowing inheritance of these traits, their genetic basis and their genes combining ability. Our study has been carried out in two directions. The first one was an assessment of hybrid combinations. The article gives the results of study of soft winter wheat hybrids of the first generation. We have presented various types of trait heritage, from negative dominance to overdominance and we have found heterosis. The second direction was an assessment of parent forms of winter wheat on total combining ability. The assessment of total (TCA) combining ability and specific combining ability (SCA) of the varieties and lines gives an opportunity to use received hybrids in breeding work planning transgressive forms in the second generation. Thus it will result in more possibility to choose forms with new valuable traits. In the result of the conducted biometrical analysis of hybrids and their parents we received a number of average indexes of the traits of 10 combinations, which was used for calculation of total and specific combining ability of initial forms. The work presents the best parent forms of soft winter wheat according to their combining ability and hybrid combinations with high specific combining ability on some quantitative traits.